Spider and mulberry silkworm silks as compatible biomaterials - Hakimi, O; Knight, D; Vollrath, F; Vadgama, P (2007)
Silks are a diverse family of natural materials with extraordinary mechanical properties such as high tensile strength and extensibility, as well as reported biological compatibility. In recent years, the reported exceptional nature of silk lead to increased interest in silk for biomedical applications. The aim of this review is to assess the potential and compatibility of silk fibres and silk-based materials for biomedical purposes. It will do so by reviewing silk properties, structure and formation, with special focus on spider and mulberry silkworm silk fibres, as well as the application of silk in the biomedical field. The review will begin by introducing the general characteristics of silk, and a consideration of properties of particular relevance to the use of silk in biomedical applications: degradation and tensile properties. Subsequently, the formation of silk in vivo will be outlined, as well as the current understanding of silk structure. A comparison of the structural differences between spider and silkworm silks will follow. Some of the different types of silk produced by orb weaving spiders, their main functions and structural features will be described. This will be followed by an introduction to 'supercontraction', a phenomenon that has only been observed in spider silks, and is considered to be one of the major obstacles to the use of native spider silk for medical applications. Finally, there will be an account of previous biomedical applications of silk. It is the intention of this review to point out the wide range of excellent and valuable properties observed in different silk types, and to propose that silk's versatility is possibly its strongest advantage. However, in the context of biomedical research and development, there are still major limitations and difficulties with native silk fibres. It is suggested in this review that an artificially produced silk or silk-like material formed to possess specific desired properties will allow the overcoming of present limitations. © 2006 Elsevier Ltd. All rights reserved.